ECG-triggered non-enhanced MR angiography of peripheral arteries in comparison to DSA in patients with peripheral artery occlusive disease - Partovi, Sasan; Rasmus, Matthias; Schulte, Anja-Carina; Rengier, Fabian; Jacob, Augustinus Ludwig; Aschwanden, Markus; Karmonik, Christof; Bongartz, Geog; Bilecen, Deniz (Magnetic resonance materials in physics, biology and medicine, 2013)
The purpose of this study was to evaluate peripheral non-enhanced-MRA (NE-MRA) acquired with a 3D Turbo Spin Echo sequence with electrocardiographt (ECG) triggering in comparison to Digital Subtraction Angiography (DSA) as the gold standard in symptomatic peripheral artery occlusive disease (PAOD) patients.
Published online: 2 November 2012
Gesehen am 20.12.2021